Pengaruh Sertifikasi Halal, Brand Image, dan Word of Mouth Terhadap Keputusan Pembelian Pada Gerai Lawson Pahlawan Trip - Zannah, Khalimatul; Khalikussabir, Khalikussabir; Athia, Ita (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research aims to test and explain the effect of halal certification, brand image, And word of mouth on purchasing decisions at Lawson Pahlawan Trip outlets. The approach used in this research is quantitative, with the research population being consumers who make transactions at Lawson outlets Jl. Pahlawan Trip. Data analysis uses multiple linear regression analysis with the help of SPSS. The research results show that halal certification does not have a significant influence on purchasing decisions, because the average visitor is a teenager who is less aware of halal certification. While brand image and word of mouth has a positive and significant influence on purchasing decisions because popular cultural trends such as K-pop and K-drama encourage consumers influenced by Korean culture to follow their community's recommendations, in line with the Japanese and Korean food concepts offered by Lawson. Keywords: Halal Certification, Brand Image, Word of Mouth, Purchase Decision